Pelaksanaan Antenatal Care Berhubungan dengan Anemia pada Kehamilan Trimester III di Puskesmas Sedayu I Yogyakarta - Fatimah Fatimah; Susi Ernawati (Alma Ata University Press, 2015)
Anemia is one of the problems in Indonesia that important to examine, especially for pregnant women. This research used quantitative with explanatory design. Population were 44 pregnant women in 3 trimester selected by the total sampling technique. The independent variable were implementation of the antenatal care by midwives and dependent variable is anemia in 3 trimester of pregnancy at Puskesmas Sedayu I Yogyakarta. Data was collected using questionnaire. The analysis used was chi-square. The results of study showed that there was 33 (75%) of antenatal care in good category, with no anemia were 32 (72.7%) respondents, and there was a significant relationship between antenatal care and anemia in the third trimester of pregnancy with p-value=0.004. In conclusion, there was a significant relationship between antenatal care and anemia in the third trimester of pregnancy. Suggestions were needed to maintain and improve the care of midwives in antenatal care to improve the health of pregnant women, especially anemia in pregnancy.